Analisis Komparatif Kinerja Reksadana Saham & Reksadana Indeks Berdasarkan Metode Sharpe, Treynor, dan Jensen - Lorencia, Maria; Taufiq, M. (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
Mutual fund get investors attention cause the risk rate are smaller than the other investment instrument, its because mutual fund are managed by a reliable party on investment called professional management. Different types of mutual funds offer different ranks of risk and return. This study use secondary data and independent sample t-test analysis technique with computer assist program SPSS 13 to compare performance between equity fund that use active management strategies and mutual fund index that use passive management strategies. Test result show that performance between equity fund and mutual fund index measured using sharpe, treynor and jensen methods are don’t have significant performance differences. So investors are free to invest their money on equity fund instrument or mutual fund index, cause its return and risk are similar.